Movement of grain to control stored-product insects and mites - White, N.D.G.; Jayas, D.S.; Demianyk, C.J. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1997)
The movement of stored grain by auger or pneumatic conveyor was evaluated for control of stored-product insects and mites. In a pilot scale test using nine welded steel bins each holding 322 kg of wheat (Triticum aestivum), movement of grain using an auger in three bins caused 89% mortality of red flour beetle, Tribolium castaneum adults and 94% mortality of rusty grain beetle, Cryptolestes ferrugineus adults. Larval mortality of both species, based on grain samples placed in Berlese funnels, was 100%. Pneumatic conveyance of grain in three bins caused 100% mortality of all stages of both insects based on grain samples and grain-probe insect traps. In field tests, infested wooden bins of wheat and corn (Zea mays) were moved by pneumatic conveyor to a truck and then hand-poured into welded steel bins. A parallel test on wheat and corn was done using a screw auger to move the grain. Pneumatic wheat movement killed 100% of mites (Aeroglyphus robustus), T. castaneum adults and larvae, and C. ferrugineus adults. Mortality of C. ferrugineus larvae and psocids was 79% and 83%, respectively. Augering wheat killed 98% of mites, 84% T. castaneum adults, 70% T. castaneum larvae, 14% C. ferrugineus adults, and 0% C. ferrugineus larvae. Pneumatic movement of corn killed 97% T. castaneum adults, 72% C. ferrugineus adults and 100% of the fungus beetle Cartodere constricta. Augering corn had less effects than pneumatic movement on insect mortality. Pneumatic conveyance of grain, especially wheat, offers an effective physical control for common stored-product insects.